Hydroxyapatite Coating On Magnesium Based Alloy For Bioimplant By Cold Spray Deposition Technique - Abdullah, Che Wan NoorAkma (2012)

(untitled)
In this study simple cold spray set up has been designed to coat AZ51 with hydroxyapatite. The details of the set up and design of the spray process has been presented. It was found that the qualities of hydroxyapatite coating were influenced by the heating temperature of magnesium substrate, surface roughness of magnesium substrate and also standoff distance. The coatings formed were compact and had good adherence to the substrate. The coating thickness varied between 20 to 30 micron meters. The chemical analysis identified the coatings as hydroxyapatite. Mechanical properties of the coatings were evaluated by nanoindentation test. The hardness and the elastic modulus of the coating were 0.1GPa and 9 GPa respectively. Further, the biocompatibility as well as biodegradation of the hydroxyapatite coated AZ51 along with uncoated AZ51 samples, were tested by subjecting them to in vitro test with simulated body fluid solutions. The inductively couple plasma optical emission spectroscopy and energy dispersive x-ray spectrometry analysis indicated that hydroxyapatite coating started dissolving after one day but showed signs of regeneration after 10 days of holding. Accelerated corrosion test in the 3.5% NaCl solution showed that the HAP coating remarkably protected the AZ51 magnesium substrate till 10 days. This continued till 21 days when most of the hydroxyapatite was replaced with magnesium hydroxide and at the end chloride ions were also detected on the surface indicating formation of magnesium chloride.